Nominative branding strategies in business and linguistic interpretation - Zbinska , Anna (Current issues of Ukrainian linguistics: theory and practice, 2024)
The author examines nominative branding strategies in the dynamics of the lavender business in Ukraine. It was determined that nominative branding strategies in business and linguistic analysis actualize multivariate criteria for choosing proper names: this generally affects the perception of the brand, its associative links with the relevant activity and the ability to attract the attention of consumers. Linguistic projection of the support of effective business is identified, which is manifested in the dynamization of branding in the representative spheres of public life. It is connected with ensuring and implementing of contacts with mass media for the purpose of brand presence on the market and in the media space, with verbalizing of the language's attractive function in the macro- and micro-context of social communication.The role and practical significance of proper names, their influence on the perception of a location or product by consumers, and the formation of a positive image of the company in the language consciousness of the recipients have been studied. The opinion that the Ukrainian lavender business is developing rapidly has been formulated and argued, and therefore, a corresponding lacuna of professional business and linguistic analysis of its nominative strategies has been formed in science. An important issue for a linguist is understanding the process of choosing an effective nomination, its semantic content. Different types of nomination, nominative models and their practical application in the context of verbalization of business strategies are considered. Attention is focused on the communicative strategies of naming, which are used to form associative ties in the process of perception by recipients of information about the brand. In addition, trends in the use of English loanwords to create a modern and attractive image of lavender brands are analyzed. The article updates the importance of nomination as an effective tool for creating and developing a recognizable business.
Keywords: nomination, communicative strategies and tactics, branding, naming, business linguistics.